2019
DOI: 10.1021/acs.jpcc.8b12216
|View full text |Cite
|
Sign up to set email alerts
|

Mass Spectrometry Study of Li2CO3 Film Growth by Thermal and Plasma-Assisted Atomic Layer Deposition

Abstract: Quadrupole mass spectrometry was carried out to detect and identify the reaction products during atomic layer deposition (ALD) of lithium carbonate (Li 2 CO 3 ). We examined gas phase species for thermal ALD using a LiO t Bu precursor together with H 2 O and CO 2 and plasma-assisted ALD using the same lithium precursor combined with an O 2 plasma. For both processes it was concluded that in the first half-cycle the LiO t Bu chemisorbs on the surface by an association reaction of the complete precursor whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…39 The fragmentation of t-BuOH in the mass spectrometer proceeds by the pathways described in The mass spectrum for LiO t Bu did not display direct fragmentations of LiO t Bu, but instead those representing t-BuOH. This was expected, as Hornsveld et al 40 also observed this in their QMS study of a Li 2 CO 3 ALD process using LiO t Bu as the lithium source. The mass spectrum of pure LiO t Bu is not available in the NIST Standard Reference Database, 39 however direct vapor phase measurements of LiO t Bu have been reported using time of flight mass spectrometry.…”
Section: Dalton Transactions Papersupporting
confidence: 55%
See 1 more Smart Citation
“…39 The fragmentation of t-BuOH in the mass spectrometer proceeds by the pathways described in The mass spectrum for LiO t Bu did not display direct fragmentations of LiO t Bu, but instead those representing t-BuOH. This was expected, as Hornsveld et al 40 also observed this in their QMS study of a Li 2 CO 3 ALD process using LiO t Bu as the lithium source. The mass spectrum of pure LiO t Bu is not available in the NIST Standard Reference Database, 39 however direct vapor phase measurements of LiO t Bu have been reported using time of flight mass spectrometry.…”
Section: Dalton Transactions Papersupporting
confidence: 55%
“…This finding is not in line with the proposed chemisorption of LiO t Bu during its initial pulse in Li 2 CO 3 and LiOH ALD processes by Cavanagh et al43 Chemisorption suggests that LiO t Bu remains intact on the surface and does not initially release volatile reaction byproducts such as t-BuOH until a subsequent H 2 O dose occurs. Hornsveld et al40 reported QMS data supporting such chemisorption behavior, in which the signal of t-BuOH (m/z 59) is negligible during LiO t Bu dose compared to a spike observed during the subsequent H 2 O pulse. In our work, a significant increase in m/z 59 is observed with repeated LiO t Bu pulses (Fig.S2 †).…”
mentioning
confidence: 94%
“…For the deposition of Li 2 CO 3 films, multiple precursor combinations and processes have been reported. These include Li-THD and O 3 , ,, LiO t Bu and O 2 -plasma ( P O 2 ), , as well as one of the several lithium precursors paired with H 2 O and CO 2 . ,, In binary processes, P O 3 and P O 2 were found to decompose the organic moieties of the lithium precursor, resulting in carbon incorporation into the film. This was not always a complete process; for example, at higher temperatures, the use of P O 2 resulted in significant Li 2 O and LiOH formation .…”
Section: Lithium-based Ald Processesmentioning
confidence: 99%
“…There are many Li ALD processes based on more than two different precursors; in most of these processes, one of the precursors is an oxygen source (H 2 O, O 3 , or both), and the most common product is a mixed oxide. As mentioned earlier, Li 2 CO 3 films have been deposited with a ternary process by pulsing H 2 O and CO 2 after the lithium precursor. ,, This mimics the natural process of LiOH conversion into Li 2 CO 3 upon exposure to ambient CO 2 . However, performing the exposure layer-by-layer in an ALD reactor allows for a better-controlled, more thorough conversion and enables the deposition of Li 2 CO 3 without the use of strong oxidizers such as O 3 or O 2 -plasma.…”
Section: Lithium-based Ald Processesmentioning
confidence: 99%
See 1 more Smart Citation